2022
DOI: 10.3389/fnagi.2022.913881
|View full text |Cite
|
Sign up to set email alerts
|

The NLR family pyrin domain containing 3 inflammasome in the mechanism of electroacupuncture: Current status and future perspectives

Abstract: Electroacupuncture, which is the most widely used alternative medicine treatment, has been gradually recognized for its effectiveness; however, its mechanism of action is not fully understood. The NLR family pyrin domain containing 3 (NLRP3) inflammasome is a thoroughly studied inflammasome that is closely associated with Alzheimer’s disease, spinal cord injury, and other diseases and plays an important role in the diagnosis and treatment of human immune system diseases. In recent years, some scholars have fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Acupuncture has emerged as a potential intervention that can regulate the gastrointestinal tract through various pathways and targets. It affects the brain–gut peptides in the body, thereby improving the brain–gut axis pathway, promoting intestinal contraction, and regulating intestinal function and motility [84]. Studies have shown that acupuncture at the ST25 (Tian shu) point can increase the expression of mesenchymal Cajal cells, which helps restore colonic smooth muscle atrophy in rats with slow-transmitting constipation.…”
Section: Discussionmentioning
confidence: 99%
“…Acupuncture has emerged as a potential intervention that can regulate the gastrointestinal tract through various pathways and targets. It affects the brain–gut peptides in the body, thereby improving the brain–gut axis pathway, promoting intestinal contraction, and regulating intestinal function and motility [84]. Studies have shown that acupuncture at the ST25 (Tian shu) point can increase the expression of mesenchymal Cajal cells, which helps restore colonic smooth muscle atrophy in rats with slow-transmitting constipation.…”
Section: Discussionmentioning
confidence: 99%
“…Only NSAIDs, which target volume-regulated anion channels, have shown good results [ 59 ]. Moreover, EA inhibits activation of the NLRP3 inflammasome through several different pathways, including the microRNA, NF-κB/NLRP3, ATP/P2X7R/NLRP3, and ROS/TXNIP/NLRP3 signaling pathways, which are related to reducing the inflammatory response [ 60 ]. In our study, EA at ST 36 significantly inhibited activation of the NLRP3 inflammasome signaling pathway in the hippocampus of 5×FAD mice, which may be directly related to its ability to reduce the proliferation and activation of microglia.…”
Section: Discussionmentioning
confidence: 99%
“…The function of TXNIP is complex and can induce both beneficial and detrimental effects under various conditions. TXNIP plays an essential role in maintaining metabolism by activating inflammatory signals in response to stimuli, such as ROS [ 12 , 13 ]. In addition, several studies have shown that TXNIP plays protective and anti-inflammatory roles [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%